ABSTRACT THE EFFECT OF MOTOR RELEARNING PROGRAM (MRP) ON THE ACTIVITY OF DAILY LIVING (ADL) LEVELS IN POST-STROKE PATIENTS - FACHRIAN AKBAR, FACHRIAN; FACHRIAN AKBAR; Addini, Ragil Aidil Fitriasari; Deasy Virka Sari (STIKES Telogorejo Semarang, 2024)
Background: A sudden disruption of blood flow in the brain area is what causes the physical disease known as a stroke to occur. As well as showing symptoms of paralysis on one side of the body, weakness with varying degrees from weak to severe, accompanied by loss of sensation, failure of the coordination system, changes in walking patterns, and balance disorders, the Motor Relearning Program (MRP) is beneficial for the recovery of the patient's motor function. It is considered effective because it can encourage the development of cognition, association, and autonomic nerves and improve standing balance in post-stroke patients. Objective: To determine the effect of the motor relearning program on increasing daily activity in post-stroke patients. Method: The research uses a quasi-experimental design with a pre-test and post-test one-group design. There were 35 samples of research respondents who met the inclusion criteria by administering the research intervention, namely a frequency of twice a week for four weeks with an action time of 15 minutes. The instrument in this research used the Barthel index to measure the activity of daily living (ADL) carried out before and after the Motor Relearning Program (MRP). Results: The results of this study using the Wilcoxon test before and after treatment obtained a p-value of 0.000, meaning a p-value of 0.05, which means Ha was accepted. Conclusion: The motor relearning program influences increased daily activities in post-stroke patients.